Evaluation of Small Extracellular Vesicles Isolation Methods from Human Serum for Downstream miRNA Profiling - Sou , Yong Ling; Tan , Paulina Pei Suu; Muhamad Hendiri , Nur Afrina; Ratnam , Wickneswari; Karupaiah , Tilakavati; Chilian , William M; Zain, Shamsul Mohd; Syed Abdul Kadir , Sharifah Zamiah; Pan , Yan; Pung, Yuh Fen (Malaysian Applied Biology, 2025)
Exosomes are a type of extracellular vesicles that carry distinct profiles of biomolecules such as lipids, proteins, DNAs, and RNAs. Despite many years of research, there is still a lack in standardized method to isolate exosomes from clinical samples for their downstream applications. Thus, this study compared three different methods, which are the differential ultracentrifugation (DUC), polyethylene glycol-based precipitation (PEG), and a combination of both (PEG+UC) to isolate exosomes from human serum. The isolated exosomes were evaluated by their size distribution, recovered particle concentration, particle to protein ratio, exosomal marker expression, and miRNA recovery. Our results indicated that all three methods successfully isolated exosomes, however, with varying yield and purity. In particular, PEG+UC produced exosomes of both high yield and high purity, DUC produced exosomes of both low yield and low purity, whereas PEG produced exosomes of high yield but low purity. Using miR-30d-5p and let-7i-5p as selected targets, our qPCR results indicated significant differences in terms of exosomal miRNA recovery between all three methods. Overall, the PEG+UC method appeared to be a less labour-intensive alternative that can isolate exosomes of both high yield and high purity from human serum without compromising the yield of miRNAs.